Análisis de alternativas de gestión ambiental para industrias del sector de alquiler de grúas hidráulicas, caso de estudio Trael S.A.S en la Calera-Cundinamarca (2021)
Through this work, we seek to carry out an analysis about solid waste management in the company TRAEL SAS, La Calera-Cundinamarca. In order to guarantee the guidelines and / or strategies to be taken into account based on the waste that is generated, in addition to achieving the reduction or use of some of them. This analysis was developed based on a diagnosis made through interviews, where distributors, quantities, qualities and other variables were provided that were used to identify the types of waste and the way in which the company handled them. This diagnosis was made both for the part of offices, secretaries and other offices of the company and also for the workshop that the company has.